Comparison of the Detection Rate and Specificity of Irregular Red Blood Cell Antibodies Between First-Time Pregnant Women and Women With a History of Multiple Pregnancies Among 18,010 Chinese Women - Shujie Wu; Yinglin Wu; Ganping Guo; Rungui Xie; Yuanjun Wu (Journal of Pregnancy)
Conclusion: Irregular RBC antibody detection is clinically important for both pregnant women with a history of multiple pregnancies and first-time pregnant women. Mur and Dia should be included in the antigenic profile of reagent RBCs that are used for performing antibody screens in the Chinese population.